Analisis Kinerja Dinas Kesehatan Kota Semarang (dalam mewujudkan Semarang Sehat) - Ardiansyah, Wildan; Widowati, Nina; Lestari, Hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
In the measurement of Human Development Index, health is one of the principal component besides education and income. Health is also an investment to support economic development and having an important role in poverty reduction efforts. View the importance of health, The Government is obliged to protect and ensure the citizens from a wide range of problems related to health. This research will analyze the performance conducted by the Dinas Kesehatan Kota Semarang and the aspects that support and hinder the performance of the Dinas Kesehatan Kota Semarang in realizing Semarang Healthy. This research uses the theory of organization and the five dimensions of performance: productivity, quality of service orientation, responsiveness, responsibility and accountability with a descriptive qualitative approach. Data collection techniques used through observation, interviews, documentation and library research with informants employee Dinas Kesehatan Kota Semarang.The result in this research showed that, the performance Dinas Kesehatan Kota Semarang in realizing Semarang Healthy is good, it's just still found problems such as human resource problems, budget funds are limited and minimal public participation. While supporting aspects of the performance Dinas Kesehatan Kota Semarang in realizing Semarang Healthy is clear jobdesk, Discipline and high responsibility owned by employee, conformity between health programs are made with what is required by the public until cooperation and coordination that exists both with the Department, NGOâ€™s and other third parties. Â Inside overcome these problems, there are some suggestions that can be done such as make education, training and skills to improve the quality of human resources, increase the number of human resources through recruitment civil servant or temporary employees that public services can be given a maximum, proposed additions of the budget in accordance with the needs required on the budget income and expenditure Semarang City and make efforts socialization to the public until they realize that health is important and expensive.Â